Compounded Topical Medications for Diseases of the Skin: A Long Tradition Still Relevant Today - Helm, MD, Matthew F.; Farah, MD, Joyce B.; Carvalho, PharmD, MRPharmS, PhD, Maria; Farah, MD, Fuad S.; Farah, MD, Ramsay S. (North American Journal of Medicine and Science, 2017)
Compounded medications remain an important component of the physicians’ armamentarium. As the volume of scientific information taught in medical school increases, the time devoted to teaching traditional treatments can at times become limited. This succinct manuscript will focus on introducing the reader to this therapeutic option and highlight some of the compounded treatments used in the management of skin diseases. [N A J Med Sci. 2017;10(3):116-118. DOI: 10.7156/najms.2017.1003116]